The hysterectomy: influence of the surgical method in benign disease on convalescence and quality of life: general gynecology - Spaich, Saskia; Weiß, Christel; Berlit, Sebastian; Hornemann, Amadeus; Sütterlin, Marc (Archives of gynecology and obstetrics, 2023)
The aim of this study was to evaluate the postoperative course after different methods of hysterectomy for benign diseases with special emphasis on time to recovery and patient-centred aspects such as postoperative quality of life and satisfaction.